Gobiernos y territorialidades: Coronda, de caserío a curato (Santa Fe, Gobernación y Obispado de Buenos Aires, 1660-1749) - Darío G. Barriera (Centre de Recherches sur les Mondes Américains, 2015)
This work analyses the concurrence of jurisdictional practices and governance between different devices (the government, the council, the bishopric) and different agents (governors, judges, neighbours, militia, their leaders, clergy or religious people, etc.) of the Hispanic Monarchy in the process of colonial occupation of Coronda. In this little town of Río de la Plata Government, which was placed ten leagues south of Santa Fe’s city, a group of territorial practices of their inhabitants let us to know how the contruction of this territory was produced between 1660 and 1749.